The Influence of Arab Culture and Technology on the Use of Code-switching in English Language Classrooms: Teachers’ Perspective - Al-Amrani, Said Nasser; Ganasan, Marcia Jane; Akkawi, Aya; Al-Abdulsalam, Malak Mohammed (Dirasat: Human and Social Sciences, 2025)
Objectives: This study explores the impact of culture and technological tools on English language teaching (ELT) in Oman, a bilingual country where English and Arabic are frequently code-switched by teachers in English-language classrooms. The aim is to understand the impact of Arab culture and digital tools on code-switching (CS) among English language teachers and their effect on language learning outcomes. Methods: The research applies Vygotsky’s sociocultural theory to examine the social and cultural dimensions of CS. A mixed-methods approach was used to collect data, including interviews and surveys with English second language educators. Descriptive and inferential statistics were used to analyze the data and identify common types of CS and factors contributing to CS in a digital environment. Results: Preliminary findings suggest that CS in English and Arabic enhances teacher-student interaction and enables the adaptation of teaching strategies. By considering the role of technology in CS practices, the study sheds light on the impact of technology on ELT classrooms. Conclusions: CS is a valuable tool in English foreign language learning (EFL) contexts, benefiting both students and teachers by enhancing engagement, reducing anxiety, and fostering dynamic learning environments. While CS supports less proficient students by integrating their native language, it should be used carefully to avoid disrupting advanced learners. Additionally, integrating technology and digital resources into EFL teaching can create immersive, personalized learning experiences, promoting self-reliance and better language acquisition. Instructors should align teaching materials with technology for optimal results.